Armies and Ecosystems in Premodern Europe : The Meuse Region, 1250-1850. - Govaerts, Sander (Amsterdam : Arc Humanities Press, 2021)
A multi-faceted and original study of the complex interactions between armies and their ecosystems, taking a long view of current debates about the environmental impact of the military.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books